FREE ANSWER ASSESSMENT METHOD IN COMPUTER SYSTEM TESTING KNOWLEDGE - Бадьоріна, Л.; Замаруєва, І. (Proceedings of National Aviation University, 2012)
The article describes students knowledge linguistic method by comparison analysis of the textual answer with given standard text and identifying their correspondence. There are given practical  settlements. Particular attention is paid to the theoretical analysis on term synomity basis by  operation with sets key words assessment linguistic method, comparison analysis